Right ovarian Endodermal sinus tumor and left ovarian Gonadoblastoma in a young female of Turner’s syndrome: a case report. - Pandey, Manju; Subedi, Hemnath; Lamichhane, Nirmal; Pandey, Greta; Shrestha, Binuma (Nepalese Journal of Cancer, 2023)
Gonadal dysgenesis includes variety of clinical condition due to abnormalities of sex chromosomes. The most frequent of this condition is Turner’s syndrome, affecting 1 in every 2000 to 2500 live births. Gonadoblastoma is a benign lesion mostly detected in individuals with dysgenetic gonads with Y chromosome and has potential for malignant transformation; or may be associated with malignant germ cell tumors, most commonly dysgerminoma or occasionally immature teratoma, endodermal sinus tumor, embryonal carcinoma, or choriocarcinoma. We report a 22-year-old girl with primary amenorrhea and physical stigmas of Turner’s syndrome presented with huge abdominopelvic mass and abdominal pain. She underwent laparotomy with TAH with BSO with appendectomy with omentectomy with resection of portion of terminal ileum with ileoileal anastomosis with resection of sigmoid colon with colorectal anastomosis and right pelvic lymph node dissection. Patient had anastomotic site leak with sepsis with multi organ dysfunction syndrome and could not be revived. Final histopathology was consistent with endodermal sinus tumor in right ovary and gonadoblastoma in left ovary. Her karyotype analysis revealed 45, X0. Endodermal sinus tumor is a highly malignant gem cell tumor with poor prognosis. Gonadoblastoma associated with endodermal sinus tumor in Turner’s syndrome is very rare and challenging for the clinical management.